If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + -3 = 1N Reorder the terms: -3 + -4y = 1N Solving -3 + -4y = 1N Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -4y = 3 + 1N Combine like terms: -3 + 3 = 0 0 + -4y = 3 + 1N -4y = 3 + 1N Divide each side by '-4'. y = -0.75 + -0.25N Simplifying y = -0.75 + -0.25N
| y-35=158 | | 12x^3-60x^2+48x=0 | | 3x+10y=4x-30 | | 12x^4-60x^2+48x=0 | | 5v/4=40 | | 12=3/7*u | | .125x-3=-9 | | 3/5*y=30 | | .3x+5=-4 | | .50x+1=7 | | x^3-5x^2+4x= | | 10N+5=4N-6 | | 11+9+7a+9a+8a= | | 5x-3=9-8x | | 2x+3.1=9.4 | | t-9=1/2 | | (21x+3)+(14x+3)=180 | | 21x+3+14x+3=180 | | -4c+17=-35 | | 7x-8y=17fory | | (7x-14)= | | 4y-4+y+54=5y+50-2y | | -7(x+8)-44=2-60 | | 14-11=x/-7 | | x-25+6=-15 | | 5x-4x-(5-4x)= | | 5x-4x-(5x-4x)= | | 6x=19-(-17) | | .66x+12+.66x=4 | | -5(x+1)-16=13+6 | | 7x-35/x^2-5x | | 2x+4=5x-13 |